L-THREONINE DECORATED PACLITAXEL POLY (L-LACTIDE) NANOPARTICLES: FORMULATION, PHARMACOKINETIC AND STABILITY STUDY - Mishra, Brijeshkunvar; Pati , Jagdish Chandra; Mishra, Richa; Saluja, Manmeet Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
A lot of research has been done on surface modification of nanoparticles to enhance the kinetics of drug release. The formulation of paclitaxel-loaded poly (L-lactide) nanoparticles conjugated with L-threonine as the surface-modifying ligand has been described in this study, along with the formulation's in vivo release kinetics in comparison to pure drug solution and stability analysis under various storage conditions. According to the study's findings, the particles had an average size of 200 nm or less, had an encapsulation efficacy of 92.6 percent, and released continuously for 24 hours. The drug's nanoparticle elimination half-life was dramatically lengthened. The most stable storage settings for the nanoparticles were determined to be in a refrigerator.